On the possible influence of the Moon and the Sun on seismic and gravimetric measurements (Proceedings of Voronezh State University. Series: Geology, 2023)
Introduction: In gravimeters and seismographs, the Golitsyn pendulum is used as a sensor, which allows more complete interpretation of seismic and gravimetric measurements. For identification of pulsations, the main difficulties arise when taking into account lunar-solar variations in gravity. Since the pulsations are global in nature, seismic and gravimetric observations at different points on the globe (in Canada (FFC), the Black Forest in Germany and Artie in Russia) were used. Processing method: The study on the isolation of pulsations of seismic vibrations showed that seismic vibrations are closely related to lunar-solar variations in gravity. The effect of the Moon and the Sun on seismic vibrations was proposed. The motion of the Moon and the Sun deform the Earth and the atmosphere, resulting in seismic vibrations. The method to take into account the influence of the Moon and the Sun on seismic vibrations of the earth was proposed. Discussion: The method to take into account the influence of the Moon and the Sun on seismic vibrations was carried out in parallel at BFO and Arti stations. Seismic measurements for 2021 were processed. The processed data, based on the morphology of seismic vibrations, showed the best match between both stations. Conclusions: It was shown that the Moon and the Sun influence the seismic vibrations of the Earth.
Keywords: gravity and seismic field pulsations; lunar-solar gravity variations; mass coronal ejections; meteor showers